Cumulative risk assessment of phthalates exposure for recurrent pregnancy loss in reproductive-aged women population using multiple hazard indices approaches. (September 2021) - Chang, Wei-Hsiang; Chou, Wei-Chun; Waits, Alexander; Liao, Kai-Wei; Kuo, Pao-Lin; Huang, Po-Chin
Highlights: Exposure to DEHP increased the risk of early recurrent pregnancy loss. Cumulative risks indices of phthalate related to early pregnancy loss. New approaches of hazard index, relative potency and receptor effect posed for female reproduction. Abstract: Phthalates, which are commonly used in flexible plastics and consumer products, have been reported to be toxic to reproductive and developmental function in mammals. Past studies have focused on the toxic effects on male reproduction, with only a few studies conducted on the risks that cumulative exposure to phthalates have on the female reproductive system. We recruited 260 patients with recurrent pregnancy loss (RPL) of unknown etiology and 203 controls from the clinics of Obstetrics and Gynecology at a medical center in southern Taiwan from 2013 to 2020. The daily intake of phthalates was estimated from urine samples using the back-calculation method, after which the cumulative risk was determined using multiple hazard indices, including a dose-addition model, a receptor effect model, and a hazard index approach. The patients with RPL had a significantly higher cumulative exposure to phthalates ( p < 0.05) than did the controls with a hazard index above one. After adjusted logistic regression analysis, we found that the risk of RPL was strongly related to the higher quartiles of DEHP, the DEHPTEQ for the antiandrogenic effect and adverse effects of the female reproductive system and the ERα binding effect ( p < 0.05). Our work suggests that more attentions should be paid to the adverse effects induced by phthalates on female reproduction, especially the effects caused by the cumulative exposure to phthalates in women of reproductive age.